Pelatihan Kurikulum 2013 Edisi Revisi 2018 bagi Guru di Yayasan Pendidikan Islam Al-Maunah - Nuryana Nuryana; Dede Cahyati Sahrir (Universitas Mathla'ul Anwar Banten, 2020)
CURRICULUM TRAINING 2013 REVISION EDITION 2018 FOR TEACHERS IN ISLAMIC EDUCATION FOUNDATIONS AL-MAUNAH. The revised curriculum edition 2013 is still not fully understood by teachers both in terms of the principle and its application. Teachers at MTs and MA Al-Maunah also felt this way. Neither the ministry of religion nor the school had involved teachers in the Curriculum 2013technical guidance. The method used in this service was through an active learning approach with multiple implementation strategies. Community service activities are carried out in five stages, namely: 1) exploration of the problems of assisted subjects; 2) workshop; 3) practice of preparing learning plans and peer teaching; 4) reel teaching in class; and 5) evaluation. The training and mentoring effort was able to change the mindset of the revised edition of the Curriculum2013 among teachers. Teachers began to have self-awareness of the shortcomings they had been doing in learning and felt they better understood how to apply the revised edition of the Curriculum 2013.